The keeper of hidden books : [large type] a novel - Martin, Madeline (Thorndike Press large print historical fiction., 2023)
"All her life, Zofia has found comfort in two things: books and her best friend, Janina. But no one could have imagined the horrors of the Nazi occupation in Warsaw. As the bombs rain down and Hitler's forces loot and destroy the city, Zofia finds that now books are also in need of saving. With the death count rising, Zofia jumps to action to save her friend and salvage whatever books she can from the wreckage, hiding them away and even starting a clandestine book club. She and her dearest friend never surrender their love of reading, even when Janina is forced into the newly formed ghetto. As Warsaw creeps closer toward liberation, Zofia must fight to save her friend and preserve her culture and community using the only weapon they have left: literature."--